Towards a Framework for Understanding the Impact of Government Policy, Family Support, Entrepreneurial Leadership, and Management Innovation on the Success of SMEs in China's Rural Communities - Liu, Junzhao; Khan, Muhammad Shahid (Journal of Neonatal Surgery, 2025)
This paper proposes a conceptual framework to understand the impact of government policy, family support, entrepreneurial leadership, and management innovation on the success of small and medium-sized enterprises (SMEs) in rural China. Through a comprehensive literature review, this study identifies key factors influencing rural SME success and explores the interrelationships among them. The proposed framework highlights the crucial role of government support in fostering a favorable environment for SME growth, the significance of entrepreneurial leadership in driving innovation and navigating challenges, the positive influence of family support on both management innovation and overall success and the importance of management innovation in enhancing organizational performance and competitiveness. This framework offers valuable insights for policymakers, SME owners, and researchers to develop effective strategies for promoting sustainable economic development in rural China.